COMPARATIVE DYNAMICS OF PROTEIN DESTRUCTION IN CANNED FOODS IN SAUCE AT DIFFERENT THERMAL TREATMENT REGIMES AND SUBSEQUENT STORAGE - V. B. Krylova; T. V. Gustova (Теория и практика переработки мяса, 2017)
In the course of investigations, the structural changes in proteins were established, which were associated with the preliminary treatment of meat ingredients, a pH level of the system and parameters of thermal treatment.The pasteurization regimes allowed retaining a protein nitrogen proportion up to 94% by the end of canned food storage duration. Upon sterilization, the losses in protein nitrogen were two times higher. A negative eﬀect of more acidic sauce on preservation of the protein nitrogen fraction in canned foods was established.An accumulation of the peptide nitrogen fraction in the canned foods in tomato sauce aﬅer pasteurization was two times more intensive. In the sterilized canned foods, the processes of accumulation of the low molecular weight nitrogenous compounds were more intensive, which suggests a depth of destruction of the protein and peptide nitrogen fraction. It was shown that an accumulation of amino-ammonia nitrogen during canned food storage was on average 12.4% irrespective of the pH value in the used sauces and the type of thermal treatment.A shiﬅ in the pH value of the canned foods toward the acid side upon pasteurization was noticed. With that, a degree of the shiﬅ in the canned foods in tomato sauce was 2.5 times higher than the pH value of the canned foods in sour cream sauce. When sterilizing canned foods, another dynamics of the pH values was observed: a pH value declined by 0.39 units in the canned foods in tomato sauce and grew by 0.22 units in the canned foods in sour cream sauce. During storage, the tendency of more intense pH decline was revealed for the canned foods in tomato sauce aﬅer pasteurization compared to the canned foods aﬅer sterilization. Another character of the pH value dynamics was found in the canned foods in sour cream sauce: an insigniﬁcant increase (by 0.7%) of the pH value in the pasteurized canned foods and a signiﬁcant decrease (by 8.4%) in the sterilized canned foods were observed by the end of storage.